O direito fundamental ao desenvolvimento e a economia criativa como alternativa à sua consecução - Pereira, Carla Sofia (2011)
The creative economy has proven to be real alternative development according to United Nations Conference on Trade walk Developmente - UNCTAD, whose pioneering work of data collection, published in 2008, and updated in 2010, spread this concept around the world. The aim of the study is to prove that the creative economy is, as adapted to the Brazilian reality, a real option for achieving the fundamental right to development conforms recommended in our Federal Constitution. To meet the proposed objective, documentary and bibliographical research was carried out as well as qualitative, using the method even if comparativo.Observou that the right to development is indeed a fundamental right and as such it is the duty and right of all, fitting active role in law, therefore, to lawyers, in search of his execution.